Reliability Level In Gadget With Student Behavior Of SMPN 36 Bulukumba - Andi Suswani; Haerati; Nini Asnidar (Jurnal Life Birth, 2020)
The gadget is an item or sophisticated tool that has been equipped with an application that can facilitate the gadget to connect to the internet. Gadgets which include almost all models and types of social media applications become a very easy tool for everyone to interact and socialize without having to be at the same time and space. Dependence on gadgets can have an impact on changes in student behavior. Because the presence of this gadget makes students cooler with their gadgets than those near them or the surrounding environment. The purpose of this research is to analyze the relationship between the level of dependence on gadgets and the behavior of students of SMPN 36 Bulukumba. The research design uses Analytical Survey with a Cross-Sectional approach. The population in this study were all students of 36 Bulukumba Senior High School who had gadgets, which were 83 respondents. With the sampling technique using the Non-Probability sampling technique with a Consecutive Sampling approach. The number of samples in this study was 47 respondents. Data obtained through questionnaires made by researchers to respondents. Data analysis using the Chi-Square Test, with a significance level of a = 0.05. The results of data analysis show that p = 0,000 is smaller than the value of a = 0.05, so Ho is rejected and Ha is accepted, meaning that there are significant results between the level of dependence on gadgets and the behavior of students of SMPN 36 Bulukumba. Conclusion: There is a relationship between the level of dependence on gadgets and the behavior of students of SMPN 36 Bulukumba.